(untitled) (Microbes and Health, 2014)
Mastitis is a serious problem for the dairy cattle in many countries of the world including Bangladesh. Among the microbial etiology bacteria plays a major role in the onset of the clinical form of the disease. Many of these bacteria are resistant to one or more antibiotics thus make the mastitis cases difficult to cure. In the present study Staphylococcus spp., Streptococcus spp., Bacillus spp. and E. coli were identified as the dominant bacterial species causing clinical mastitis in cattle in Mymensingh. Antibiogram study revealed chloramphenicol and erythromycin as the most effective antibiotic for the treatment of mastitis in these animals except those caused by Bacillus spp. and E. coli, respectively. Microbes and Health, June 2013, 2(1): 19-21 DOI: http://dx.doi.org/10.3329/mh.v2i1.17258